Guest Speaker for The International Seminar and Global Learning System GLS Program with Binus University - Yusof, Yuhani; Mohd Sham, Mohamad; Ahmad Fuad, Amirul Aizad (2023)
Heartiest congratulations to the three academicians from the Discrete Mathematics panel; Assoc. Prof. Dr. Mohd Sham Mohamad, Assoc. Prof. Dr. Yuhani Yusof and Dr. Amirul Aizad Ahmad Fuad for their contributions as the Guest Speaker for the International Seminar and Global Learning System (GLS) Program with BINUS University, Indonesia between 20-21st March 2023.